DESIGN AND EVALUATION OF BOSENTAN CONTROLLED-RELEASE MICROCAPSULES - KOREDDI, HARSHA; SURYADEVARA, VIDYADHARA; TALAMANCHI, BALAKRISHNA; ANNE, RAMU (International Journal of Applied Pharmaceutics, 2022)
Objective: The objective of the present work is to formulate and evaluate Bosentan controlled-release microcapsules using gum karaya and polyethylene oxide as polymers, sodium alginate and calcium chloride as encapsulating material and cross-linking agent and croscarmellose sodium as superdisintegrant. Methods: Bosentan microcapsules were prepared by the ionic gelation method. The prepared microcapsules were characterized by flow properties such as angle of repose, compressibility index, particle size and encapsulation efficiency and drug release profiles. Results: The prepared microcapsules were evaluated for angle of repose, compressibility index, % drug content, encapsulation efficiency and particle size. All the flow properties were within the specified IP limits. The drug content of microcapsules prepared by ionic gelation method by varying the polymeric concentration was found in the range of 121.62±0.41 to 124.99±0.51 mg. The encapsulation efficiency of Bosentan controlled-release microcapsules was found to be in the range of 59 % to 67%. Among all the formulations prepared, formulation B14 containing equal proportions (25 mg) of gum karaya and polyethylene oxide showed about 95% of drug release over a period of 12 h and were found to be suitable for extending drug release up to 16 h. Conclusion: Bosentan controlled-release microcapsules were prepared by ionic gelation method, which is a novel formulation that is helpful in the treatment of pulmonary artery hypertension (PAH).